Customer Relationship Management Strategies in Developing the Brand Image of Secondfloor Coffee Bintaro - Fidya Okctafiani Putri; Tria Patrianti (CV. Civiliza Publishing, 2025)
In an era of increasingly competitive culinary business, the role of communication strategy and customer relations is crucial in shaping a strong and memorable brand image. This research aims to determine the customer relations strategy implemented by Secondfloor Coffee Bintaro in building and strengthening its brand image. This study uses a descriptive qualitative methodology with data collection techniques in the form of in-depth interviews, participatory observation, and documentation. The informants in this study consisted of management, supervisors, staff, and competitors for triangulation purposes. The study employs Customer Relations Management theory, which includes three main indicators: customer profile identification, communication, and complaint handling. For brand image, it refers to theory that encompasses brand strength, brand uniqueness, and brand appeal. The results show that Secondfloor Coffee Bintaro has implemented a customer relations strategy through a personal approach, responsive service, and active two-way communication both directly and via social media. This strategy has successfully created positive customer experiences and built trust, loyalty, and a strong brand image in the minds of consumers, particularly among young people. Nonetheless, some challenges remain, such as the perception of high prices and limitations in supporting facilities that need to be addressed. This research concludes that an effective customer relations strategy can significantly support the strengthening of a cafe's brand image amidst food and beverage industry competition. The implications of this research are expected to serve as a strategic reference for culinary business players in enhancing customer relations and building a positive and sustainable brand image.